Polymorphous corneal dystrophy subtype 3 and keratoconus aggravation after corneal refractive surgery in a three-generation family carrying both ZEB1 and ZNF469 pathogenic variant - Lin, Qinghong; Wang, Xuejun; Peng, Xiaoliao; Han, Xiaosong; Zhang, Xiaoyu; Sun, Ling; Wang, Yan; Liu, Shengtao; Zhou, Xingtao (Frontiers in Genetics, 2025)
BackgroundThis study reports a three-generation Chinese family with polymorphous corneal dystrophy subtype 3 (PPCD3) and keratoconus (KC) aggravation induced by corneal refractive surgery, specifically small incision lenticule extraction (SMILE), in the context of genetic variations.MethodsThe history of illnesses and blood samples of all family members were collected. One hundred healthy individuals served as normal controls. We conducted whole exome sequencing on genomic DNA and sanger sequencing to verify the variants between all controls and family members.ResultsThree family members were previously diagnosed with subclinical keratoconus (III1 and III2 preoperatively, and II2). Both the proband (III1) and her younger brother (III2) underwent SMILE to correct refractive errors. One year later, visual acuity of III1 decreased significantly with KC aggravation and corneal opacification. The KC of III2 progressed significantly 6 months after surgery. Both were subsequently diagnosed with PPCD3. We detected both Zinc finger E-box-binding homeobox 1 (ZEB1) gene and zinc finger protein 469 (ZNF469) gene pathogenic variant in the proband and another two patients in this family, including a heterozygous missense variation c.13C>G (p.P5A, rs753301298) in the ZEB1 gene, and a heterozygous non-frameshift variant c. 3093_3104del (p.D1035_K1038del) in the ZNF469 gene. The variants including c.13C>G in ZEB1 and c.3093_3104del in ZNF469 were speculated to be pathogenic or a variant of uncertain significance by online prediction software.ConclusionThis study demonstrated the importance of a thorough ocular examination, especially the cornea, and a gene screening before SMILE.